2019
DOI: 10.1108/ijhcqa-02-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture in Hungarian hospitals

Abstract: Purpose The Hospital Survey on Patient Safety Culture (HSOPSC) is a rigorously designed tool for measuring inpatient safety culture. The purpose of this paper is to develop a cross-cultural HSOPSC for Hungary and determine its strengths and weaknesses. Design/methodology/approach The original US version was translated and adapted using existing guidelines. Healthcare workers (n=371) including nurses, physicians and other healthcare staff from six Hungarian hospitals participated. Answers were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
3
14
0
5
Order By: Relevance
“…POPSC1 deals with reciprocal interpersonal respectfulness of the staff toward each other and the importance of their team work. The obtained results are consistent with some studies [39,40], that highlight the importance of POPSC1 in promoting patient safety culture. Consequently, it may be concluded that team work ought to be performed appropriately.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…POPSC1 deals with reciprocal interpersonal respectfulness of the staff toward each other and the importance of their team work. The obtained results are consistent with some studies [39,40], that highlight the importance of POPSC1 in promoting patient safety culture. Consequently, it may be concluded that team work ought to be performed appropriately.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the rate of error-related events were reported to be fewer after educational intervention compared to before intervention; still, this rate increased 1 month after completion of intervention. Anyway, the results of most similar studies demonstrated a low rate of error report by nurses so that in the study by Granel et al, 66% of individuals reported no medical error over the past year [39]. The results of the study by Azimi Aqdas et al showed that most nurses (52.7%) reported no medical errors over the past 12 months [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that most European studies examining the psychometric properties of the HSOPSC questionnaire, resulted in reliable and valid models with fewer than the 12 dimensions of the original US HSOPSC structure. 5,7,8,2832 Therefore, it is common for the original US HSOPSC 12-scales model to be adapted in order to incorporate each country’s relevant patient safety cultural aspects. Similarly to other studies, our results showed that the ‘Non-Punitive Response to Error’ scale (Scale 7) had a weak internal consistency.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, continuously assessing and improving patient safety culture are of strategic importance for the credibility of healthcare providers. 35 To achieve this, several scientific instruments have been developed and evaluated, such as the Hospital Survey on Patient Safety Culture (HSOPSC). 58 In Greece, the recent economic recession and the dramatic Gross Domestic Product drop have led to reduced healthcare expenditure, shortages in healthcare professionals and medical supplies, immense patients’ shift towards public healthcare structures, thus jeopardizing the provision of quality care.…”
Section: Introductionmentioning
confidence: 99%
“…The HSOPSC, developed in English [28] for use in American hospitals, has demonstrated excellent psychometric properties [27]. The instrument has been disseminated to other countries, in multiple languages [8,24,[30][31][32][33][34][35][36]; however, published studies generally neglect to report the instrument translation method and validation data. When provided, the information is either limited or poor quality such as reporting a simple post hoc psychometric analysis.…”
Section: Introductionmentioning
confidence: 99%